Seeing the invisible hand: Underlying effects of COVID-19 on tourists’ behavioral patterns - Li, Zhiyong; Zhang, Shan; Liu, Xinyi; Kozak, Metin; Wen, Jun (Journal of destination marketing & management, 2020)
Given growing attention toward the effects on COVID-19 on tourism, a number of institutions have made macro-level predictions related to the disease. More micro-level research are, however, needed. This study seeks to advance the understanding of tourists' potential behavioral transformation by reviewing psychological distance and construal level theory, as well as the relationship between psychological distance and perceived risk. Multiple dimensions of psychological distance and perceived risk are summarized with respect to COVID-19. The discussion suggests that global health emergencies evoke three types of tourism pattern: from general to elaborate, from open-hearted to closed, and from radical to conservative. These categories provide a conceptual foundation for empirical research considering contextual and individual stimuli. Practically, this paper highlights strategies to reduce individuals’ risk perceptions, encourage specific types of tourism, and regulate unethical consumption. The recommendations also encourage the analysis of crisis recovery and relevant market analysis by tourism professionals and marketers. •Uses the rationality of applying psychological distance and construal level theory to tourism research on COVID-19.•Investigates the mechanism between psychological distance and perceived risk.•Identifies tourists' psychological distance dimensions and perceived risks.•Summarizes the transformation of tourists' behavior patterns after the outbreak of COVID-19.•Proposes research opportunities based on the conceptual model put forth in this paper.